Pencacah Ikan Mekanis Meningkatkan Produktivitas Perajin Cacahan Ikan di Desa Hajoran Tapanuli Tengah - Anizar Anizar; M. Zainul Bahri Torong; Idhar Yahya (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2018)
Marine fisheries sector is a source of community livelihood in the coastal area. Hajoran village in Tapanuli Tengah district is a coastal area with great potential in fishery sector, especially marine fishery. Fisherman Hajoran uses a rectangular bamboo arrangement measuring 10m x 10m which is plugged in the middle of the waters to catch fish. Some of the fish are sold in fresh condition while others are salted. The salted fish only sold the body parts while the salted fish head will be chopped into smaller pieces by the artisans. The process of enumeration is done using a machete with a work posture sitting bent, bent knees and bent legs. Crafters complain of pain on the wrist, shoulders, waist, buttocks and knees so difficult to be able to stand up after the enumeration process is complete. Fish replicating craftsmen provide input in the form of SNQ questionnaires to analyze their grievances over the years. The activity takes a long time, the quality of fish count is not uniform, low production capacity and cause pain in the limbs. Community service activity is aimed at increasing the productivity of shrimp fish craftsman. The effort is accompaniment by the ergonomics team, the giving of lecture materials, the training of ergonomic work facility and the improvement of working method so that the active participation of crafters is needed. Utilization of mechanical fish counter is a solution to increase the productivity of fish crackers. The resulting fish yields will have an adjustable subtlety, good quality, short time and ergonomic design. Improvement of work methods performed by the team of devotion causes the crafters to work more comfortable resulting in increased productivity.